Predisposing Factors of Recidivism as Perceived by Prison Officers in Kwara State, Nigeria: Implications for Counselling Practice - Adegboyega, Lateef Omotosho (Universitas Pendidikan Indonesia, 2020)
ABSTRACT: Descriptive survey design was adopted for the study and a researcher-designed questionnaire tagged PFRQ (Predisposing Factors of Recidivism Questionnaire) was used to obtain relevant information. Multi-stage sampling technique was adopted to select 250 prison officers from all the five prison centers in Kwara State, Nigeria. Findings showed that prison officers perceived factors, such as non-availability of employment opportunities for ex-convicts, problem of where to start a new life after release from prison among others. The results, further, revealed significant difference in predisposing factors of recidivism as perceived by prison officers based on years in service, but no significant difference was found based on gender. It was recommended that counsellors should endeavour to beam their searchlight into issues of crime, imprisonment, and recidivism; counsellors should also liaise with different NGOs (Non-Governmental Organizations), including faith-based to assist released offenders to achieve ease of re-integration into the society.KEY WORD: Predisposing Factors; Recidivism; Prison Officers; Kwara State in Nigeria.Â ABSTRAKSI: â€œFaktor-faktor Predisposisi Residivisme yang Dipersepsikan oleh Petugas Penjara di Negara Bagian Kwara, Nigeria: Implikasi bagi Praktek Konselingâ€. Desain survei deskriptif diadopsi untuk penelitian ini dan kuesioner yang dirancang oleh peneliti yang diberi label PFRQ (Faktor-faktor Predisposisi Kuesioner Residivisme) digunakan untuk memperoleh informasi yang relevan. Teknik pengambilan sampel multi-tahap diadopsi untuk memilih 250 petugas penjara dari semua lima pusat penjara di Negara Bagian Kwara, Nigeria. Temuan menunjukkan bahwa petugas penjara memahami faktor-faktor, seperti tidak tersedianya kesempatan kerja bagi mantan narapidana, masalah dimana memulai kehidupan baru setelah dibebaskan dari penjara antara lain. Hasilnya, lebih lanjut, mengungkapkan perbedaan signifikan dalam faktor predisposisi residivisme seperti yang dirasakan oleh petugas penjara berdasarkan tahun dalam pelayanan, tetapi tidak ada perbedaan signifikan yang ditemukan berdasarkan jenis kelamin. Dianjurkan agar konselor harus berusaha untuk memberikan sorotan mereka kedalam masalah kejahatan, penjara, dan residivisme; konselor juga harus bekerja sama dengan berbagai LSM (Lembaga Swadaya Masyarakat), termasuk berbasis agama, dalam membantu pelanggar yang dibebaskan untuk mencapai kemudahan integrasi kembali kedalam masyarakat.KATA KUNCI: Faktor Predisposisi; Residivisme; Petugas Penjara; Negara Bagian Kwara di Nigeria.About the Author: Lateef Omotosho Adegboyega, Ph.D. is a Lecturer at the Department of Counsellor Education, Faculty of Education UNILORIN (University of Ilorin), Ilorin, Nigeria. For academic interests, the Author is able to be contacted via e-mails adrress at: adegboyega.lo@unilorin.edu.ng and adegboyegalateef@gmail.comÂ Â Â Â Â Suggested Citation: Adegboyega, Lateef Omotosho. (2020). â€œPredisposing Factors of Recidivism as Perceived by Prison Officers in Kwara State, Nigeria: Implications for Counselling Practiceâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Volume 5(1), March, pp.1-14. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Article Timeline: Accepted (January 15, 2020); Revised (February 21, 2020); and Published (March 30, 2020).